DevOps workflow verification and duration prediction using non‐Markovian stochastic Petri nets. Issue 3 (3rd December 2020) - Ben Mesmia, Walid; Escheikh, Mohamed; Barkaoui, Kamel
Abstract: In this paper, we provide a non‐Markovian Stochastic Petri Net (SPN) model for D e v O p s w o r k f l o w specification, and we determine how business processes are carried out. After describing our model semantics, we show how general properties related to liveness and safety can be checked. After that, we provide several extensions on S P N s (SPN) the notation and expressivity to check some specific properties related to actors' (Developers and Operators) availability, interactions between the actors, and execution failures detection linked to the D e v O p s steps. Next, we validate the proposed model relevance with M A T L A B simulation through a specific D e v O p s case study. Finally, we propose a truncated density function to anticipate the delays related to the D e v O p s business process overall steps.